GOOGLE MAPS AND MAPBOX API PERFORMANCE ANALYSIS ON ANDROID-BASED LECTURE ATTENDANCE APPLICATION - Kurnia Saputra; Muhammad Furqan; Taufik Fuadi Abidin; Dalila Husna Yunadi (Jurnal Natural, 2019)
Attendance is an inseparable component from lectures. The current manual attendance process still has its weaknesses, such as the loss or broken attendance sheets, the easiness to conduct fraud on the attendance sheets, and other cases. The attendance system using fingerprint devices are also not available in other locations yet, such as lectures that are done on the field or outdoor, where fingerprint devices are not available. Because of that, an online lecture attendance system that makes use of Android-based smartphones is developed in order to tackle the problem. This online lecture attendance system has the main feature of recording students’ attendances in a radius of 300 metres from the lecturer. This application is named Lecture Attendance System is developed using Rapid Application Development (RAD) model, because it is an effective method to minimise errors in the application. There are two testing performed to the application. The first testing was functional testing of the application. This testing was carried out in order to make sure that all functionalities and features are performing well. The second testing carried out is the distance accuracy testing, to compare between the Google Maps and MapBox API distances. From this testing, it was found that the error percentage using Google Maps is 9.250% and 12.128% for MapBox. From these results, they show that in calculating the distance, using Google Maps API has higher accuracy compared to the MapBox API.